Detection of β-lactamase genes and characterization of class 1 integrons in multidrug-resistant Pseudomonas aeruginosa strains in Guilan, Iran - Tahereh Panahi; Leila Asadpour; Najmeh Ranji (Medical Laboratory Journal)
Background: Infections caused by extended-spectrum β-lactamase (ESBL)-producing Pseudomonas aeruginosa (P. aeruginosa) are a serious concern in hospitals around the world. Many β-lactamase genes are carried by integrons. This study was conducted to investigate the frequency of β-lactamase genes and characterize class 1 integrons in multidrug-resistant P. aeruginosa strains in Guilan, northern Iran. Methods: A total of 110 P. aeruginosa isolates were collected from different hospitals in 2021 and identified using standard microbiological methods. The isolates were studied for their antibacterial susceptibility and ESBL-producing ability by disk diffusion. All ESBL-producing isolates were investigated for the presence of β-lactamase resistance and integron genes by polymerase chain reaction (PCR). Gene cassette screening was done based on sequence analysis of class 1 integrons. Results: Based on antibiotic susceptibility testing, 40 isolates (37.4%) were ESBL producers. The frequency of β-lactamase genes, including VIM, SIM, IMP, SPM, and OXA2, was 10.3%, 1.9%, 20.6%, 14%, and 4%, respectively. GIM and OXA 10 genes were not found in any of the strains. Furthermore, the int1 gene was identified among 37 isolates (34.6%). The sequencing results of int1 showed 12 different types of gene cassettes among 13 strains. In this assay, blaOXA-2 was the only bla gene identified in int1. Conclusion: The integrons carrying multidrug resistance genes are highly prevalent in P. aeruginosa isolates, and ESBL genes were also observed in these strains. Therefore, constant monitoring of drug resistance, especially ESBL producers, is critical to disease management in clinical settings.